2007
DOI: 10.1348/014466506x158996
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Depression Anxiety Stress Scales (DASS) in depressed clinical samples

Abstract: The psychometric properties of the DASS were sound in clinically depressed samples, but the Depression Scale exhibited a ceiling effect that could not be resolved with minor changes to the scale. Suggestions for revisions of the DASS are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
181
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(204 citation statements)
references
References 28 publications
17
181
3
3
Order By: Relevance
“…For instance, one study with a clinical sample found that the DASS-21 accurately distinguishes between individuals with mood disorder, panic disorder or obsessivecompulsive disorder (Page, Hooke, & Morrison, 2007). Participants were asked to indicate how frequently in the preceding week they had experienced symptoms such as "I felt like I wasn't worth much as a person", (depression subscale, α=.88), "I felt I was close to panic" (anxiety subscale, α=.81) and "I tended to over-react to situations" (stress subscale, α=.84) from 0 "Did not apply to me at all" to 3 "Applied to me very much, or most of the time".…”
Section: Depression Anxiety Stress Scales (Dass-21)mentioning
confidence: 99%
“…For instance, one study with a clinical sample found that the DASS-21 accurately distinguishes between individuals with mood disorder, panic disorder or obsessivecompulsive disorder (Page, Hooke, & Morrison, 2007). Participants were asked to indicate how frequently in the preceding week they had experienced symptoms such as "I felt like I wasn't worth much as a person", (depression subscale, α=.88), "I felt I was close to panic" (anxiety subscale, α=.81) and "I tended to over-react to situations" (stress subscale, α=.84) from 0 "Did not apply to me at all" to 3 "Applied to me very much, or most of the time".…”
Section: Depression Anxiety Stress Scales (Dass-21)mentioning
confidence: 99%
“…However, to do so they need a validated measure. The Depression Anxiety Stress Scale (DASS) is a frequently used measure (1) with good psychometric properties (2) . It has a demonstrated ability to discriminate between clinical and nonclinical groups (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Moderate level cut-offs (Depression ≥ 7, Anxiety ≥ 5, Stress ≥ 10) are representative of clinical populations (Lovibond & Lovibond, 1995;Ronk, Korman, Hooke, & Page, 2013). The instrument has good to excellent internal consistency (Cronbach's α = 0.82-0.94), good criterion validity, acceptable discriminant validity, moderate sensitivity to clinical change, and acceptable to good temporal stability (r = 0.71-0.81) in clinical samples (Antony et al, 1998;Brown, Chorpita, Korotitsch, & Barlow, 1997;Henry & Crawford, 2005;Ng et al, 2007;Page, Hooke, & Morrison, 2007).…”
Section: Methodsmentioning
confidence: 99%